2013
DOI: 10.1007/s00449-013-0978-3
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of an activated sludge model for greenhouse gases no. 1 (ASMG1): prediction of temperature-dependent N2O emission dynamics

Abstract: An activated sludge model for greenhouse gases no. 1 was calibrated with data from a wastewater treatment plant (WWTP) without control systems and validated with data from three similar plants equipped with control systems. Special about the calibration/validation approach adopted in this paper is that the data are obtained from simulations with a mathematical model that is widely accepted to describe effluent quality and operating costs of actual WWTPs, the Benchmark Simulation Model No. 2 (BSM2). The calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 22 publications
2
70
0
1
Order By: Relevance
“…The authors confirmed the importance of using plant-wide modelling and stressed the need for setting up dedicated databases for reliable and feasible WWTP analysis at the plant-wide scale. During the last years, the interest in moving towards a wastewater treatment plant-wide control (including GHG) with the use of BSM was emphasized in literature (Guo et al, 2012;Guo and Vanrolleghem, 2014;Kim et al, 2015b) (Fig. 1).…”
Section: Brief Historical Overview Of Plant-wide Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors confirmed the importance of using plant-wide modelling and stressed the need for setting up dedicated databases for reliable and feasible WWTP analysis at the plant-wide scale. During the last years, the interest in moving towards a wastewater treatment plant-wide control (including GHG) with the use of BSM was emphasized in literature (Guo et al, 2012;Guo and Vanrolleghem, 2014;Kim et al, 2015b) (Fig. 1).…”
Section: Brief Historical Overview Of Plant-wide Modellingmentioning
confidence: 99%
“…The approaches for GHG modelling can be grouped (Corominas et al, 2012): i) empirical models based on the emission factors at the treatment unit scale (e.g., IPCC, 2006;LGOP, 2008); ii) simple comprehensive process-based models at the treatment unit scale (e.g., Monteith et al, 2005;Gori et al, 2011); iii) dynamic mechanistic models at the treatment unit (e.g., Mannina and Cosenza, 2015) or plant-wide scale (e.g., Guo and Vanrolleghem, 2014).…”
Section: Previous Studies Of Ghg Modelling At the Plant-wide Scalementioning
confidence: 99%
See 3 more Smart Citations